Knowledge, skills and attributes for academic reference librarians - Haddow, Gaby (Australian Library and Information Association, 2012)
A survey of Australian academic reference librarians was conducted as part of an international collaboration seeking to identify the most important knowledge, skills and attributes now and for the next ten years. Librarians working in or managing reference-related services at university and vocational education and training institutions participated in the online survey. Their responses indicate that a core professional skill, searching, is the most important skill for reference librarians, followed by other generic skills, such as verbal communication and customer service skills.